Financial statement analysis - Fridson, Martin S (John Wiley & Sons, 2011)
Includes bibliographical references and index; "An updated guide to the essential discipline of financial statement analysis. In Financial Statement Analysis, Fourth Edition, leading investment authority Martin Fridson returns with Fernando Alvarez to provide the analytical framework you need to scrutinize financial statements, whether you're evaluating a company's stock price or determining valuations for a merger or acquisition. This fully revised and up-to-date Fourth Edition offers fresh information that will help you to evaluate financial statements in today's volatile markets and uncertain economy, and allow you to get past the sometimes biased portrait of a company's performance. Reflects changes in the financial reporting landscape, including issues related to the financial crisis of 2008-2009. Provides guidelines on how to interpret balance sheets, income statements, and cash flow statements. Offers information for maximizing the accuracy of forecasts and a structured approach to credit and equity evaluation. Filled with real-life examples and expert advice, Financial Statement Analysis, Fourth Edition will help you gain a firm understanding of the techniques that will help you interpret financial statements, which are designed to conceal more than reveal."-- Provided by publisher